0574 Phenotypic Predictors of Long-Term Upper Airway Neurostimulation Responsiveness in the ADHERE International Registry. (12th April 2019) - Strollo, Patrick J; Soose, Ryan J; Doghramji, Karl; Stevens, Suzanne; Waters, Tina; Schwab, Richard; Withrow, Kirk; Manchanda, Shalini
Abstract: Introduction: Upper airway neurostimulation (UAS) is an effective treatment for CPAP-intolerant obstructive sleep apnea (OSA). We leveraged the FDA post-approval international ADHERE registry to examine phenotypic predictors of UAS responsiveness. Methods: Patients undergoing UAS implantation in the US and Germany from October 2016 through November 2018 were enrolled in an observational registry. Demographics, sleep study-based data: Apnea Hypopnea Index (AHI), Epworth Sleepiness Scale (ESS) and objective adherence were collected at baseline, implant, and 6- and 12- month post-implantation. Paired t-tests were used to compare between visits. Univariate and multivariate logistic regression models (odds ratio and 95% confidence intervals) were constructed including age, sex, body mass index (BMI), AHI and adherence to examine impact of UAS therapy on response defined by 50% or more reduction in AHI and AHI < 20 at the 12-month visit. Results: Of 837 patients enrolled, 565 have completed 6-month follow-up, and 334 have completed 12-month follow-up. Average age was 60 ± 11 years, BMI of 29.3 ± 3.9 kg/m 2, 74% male and 96% Caucasian. After 12-months, median AHI was reduced from 33 (IQR: 24 - 46) to 9 (IQR:4-18). (Mean: 36.3±15.6 to 13.4 ± 14.3, p < 0.0001). Median ESS was improved from 11.0 (IQR: 7.0-16.0) to 6.0 (IQR: 3.0-10.0) (mean: 11.6 ± 5.5 to 7.1 ± 4.8, p < 0.0001). In 70% of the patients, AHI was reduced to less than 15 events/hour. Therapy usage was 5.6 ± 2.1 hours/night. Female sex (OR= 4.8, 95% CI: 1.6, 14.3) and lower baseline BMI (OR=0.91, 95% CI 0.85 - 0.98) were significant predictors of therapy response. Females were older than males (63 ± 10 years vs 59 ± 12, p < 0.0001). Females older than 65 had a higher response rate than similarly aged males (p=0.02), however, females represented 9% of the study population. Conclusion: Female sex and lower BMI are predictors of long-term UAS response after adjustment for adherence, suggesting a potential biologic mechanism. UAS has durable impact on OSA outcomes with a high level of adherence. Support (If Any): Inspire Medical Systems